IMPLEMENTASI TERAPI KOMPLEMENTER BAWANG PUTIH PANGGANG DAN RELAKSASI NAFAS DALAM PADA LANSIA HIPERTENSI DI POSBINDU KELURAHAN PASIR JAYA KOTA BOGOR - Anna Sunita; Susmadi Susmadi; Eti Surtiati; Nieniek Riftianingsih (Poltekkes Kemenkes Bandung, 2022)
Hypertension is one of the non-communicable diseases (NCDs) that many people suffer from in general, and most of the elderly. People with hypertension are estimated to be 1 billion globally. Two-thirds of them are in developing countries. This figure continues to rise sharply and predicted that by 2025 around 29% of adults worldwide suffer from hypertension. Control and management of hypertension with pharmacology used by sufferers in the long term can cause saturation, irregularly take medicine, and will stop taking medication when symptoms have decreased. Hypertension persists and further complications will occur in the target organ. Management of non-pharmacological hypertension needs to be offered to people with hypertension, in the form of complementary therapy of slow deep breathing and herbal treatment in the form of consumption of roasted garlic. Patients with hypertension with locations in 2 Rukun Warga (RW) Pasir Jaya Village, Bogor City totalled 34 people, including 6 cadres from two RWs in Pasir Jaya Village. Training on cadres was carried out and at the same time, health education for hypertensive elderly on procedures for relaxing deep breathing and eating roasted garlic. And carried out assistance for approximately 1 month for the two locations including RW. 08 and RW. 10 Pasir Jaya Village, Bogor City. The results of the implementation of deep breath relaxation therapy and consumption of roasted garlic in hypertension sufferers in the working area of the Pancasan Health Center, West Bogor District, Bogor City, can reduce the blood pressure of people with hypertension, both systole and diastole (p-value = 0.000).